Introduksi Produk Olahan Ubi Jalar Pada Anggota Ika Tanjung Sakti, Bandar Lampung - Neti Yuliana; Dewi Sartika; Samsu Udayana Nudin; Novita Herdiana; Pramita Sari Anungputri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Sweet potato is a non-rice carbohydrate food that has health and nutritional benefits, so it needs to be disseminated in the community. This community extention program aimed to increase the understanding of the target community regarding the diversification of sweet potatao processing into various rice substitution products, as well as providing knowledge of the benefits of sweet potato from the nutritional and health aspects. The participant audiences was the Tanjung Sakti IKA group members, Sukarame, Bandar Lampung. The method used was lecture, discussion, and evaluation. The results of the activity showed that the change percentage in participants' knowledge about the benefits of sweet potatoes increased by 85%, and that about the processed sweet potato products by 67-100% depending on the type of product. In general, participants consider counseling or introduction of sweet potatoes was useful. Keywords: Tanjung Sakti IKA, health and nutritional benefits, processed products, sweet potatoes